Nd-Yag laser treatment of glans penis hemangioma. Case report. - Amaro, João Luiz [UNESP]; Agostinho, Aparecido Donizeti [UNESP]; Polido, A.; Costa, R. P.; Trindade Filho, José Carlos Souza [UNESP]; Trindade, J C S (Masson Editeur, 1997)
Hemangioma of urinary tract are unusual, being about 2 % of all hemangiomas. We present a case of a glans penis hemangioma. There is controversy concerning their treatment and outcome. Our patient was treated with a Neodymium : Yag laser irradiation, with complete morphological recuperation.
Keywords: hemangioma; glans penis; Nd-Yag laser treatment